Specific features of sublimation growth of bulk AlN crystals on SiC wafers. Issue 3 (15th January 2013) - Mokhov, E.; Izmaylova, I.; Kazarova, O.; Wolfson, A.; Nagalyuk, S.; Litvin, D.; Vasiliev, A.; Helava, H.; Makarov, Yu.; Toropov, Alexey; Ivanov, Sergey
Abstract The features of 2" AlN bulk crystal growth by the sublimation sandwich method (SSM) on SiC seeds in a graphite‐heated reactor are investigated. AlN growth conditions and crystal properties are compared with the results of SiC sublimation growth in the same reactor. The specifics of AlN sublimation growth, including insufficient reproducibility of results, are believed to be caused by the low sticking coefficient of molecular nitrogen and the high reactivity of Al vapors. The formation of pores in the AlN crystal is explained by selective sublimation etching of the growing surface. The negative effect of non‐optimal growth conditions and impurities on AlN crystal quality is discussed. The analysis of container materials, inert to Al vapors was carried out. Various types of TaC crucibles suitable for growth of bulk AlN crystals on SiC seeds were developed. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)